Longer days enable higher diurnal activity for migratory birds. Issue 9 (29th March 2021) - Pokrovsky, Ivan; Kölzsch, Andrea; Sherub, Sherub; Fiedler, Wolfgang; Glazov, Peter; Kulikova, Olga; Wikelski, Martin; Flack, Andrea
Abstract: Seasonal geophysical cycles strongly influence the activity of life on Earth because they affect environmental conditions like temperature, precipitation and day length. An increase in daylight availability during summer is especially enhanced when animals migrate along a latitudinal gradient. Yet, the question of how day length (i.e. daylight availability) influences the activity patterns of long‐distance, latitudinal migrants is still unclear. Here, we ask whether migration provides benefits to long‐distance migrants by enabling them to increase their diurnal movement activities due to an increase in daylight availability. To answer this question, we tested whether four vastly different species of long‐distance migratory birds—two arctic migrants and two mid‐latitude migrants—can capitalise on day length changes by adjusting their daily activity. We quantified the relationship between daily activity (measured using accelerometer data) and day length, and estimated each species' daily activity patterns. In addition, we evaluated the role of day length as an ultimate driver of bird migration. All four species exhibited longer activity periods during days with more daylight hours, showing a strong positive relationship between total daily activity and day length. The slope of this relationship varied between the different species, with activity increasing 1.5‐fold on average when migrating from wintering to breeding grounds. Underlying mechanisms of these relationships reveal two distinct patterns of daily activity. Flying foragers showed increasing activity patterns, that is, their daytime activities rose uniformly up to solar noon and decreased until dusk, thereby exhibiting a season‐specific activity slope. In contrast, ground foragers showed a constant activity pattern, whereby they immediately increased their activity to a certain level and maintained this level throughout the day. Our study reveals that long days allow birds to prolong their activity and increase their total daily activity. These findings highlight that daylight availability could be an additional ultimate cause of bird migration and act as a selective agent for the evolution of migration. Abstract : The authors study reveals that long days allow birds to prolong their activity and with it increase their total daily activity. These findings highlight that daylight availability could be an additional ultimate cause of bird migration, and act as a selective agent for the evolution of migration. Resumen: Los ciclos geofísicos estacionales influyen fuertemente la actividad de la vida en la Tierra ya que afectan diversas condiciones ambientales como la temperatura, la precipitación y la duración del día. El aumento de la disponibilidad de luz solar durante el verano favorece especialmente a las especies que migran a lo largo de un gradiente latitudinal. Sin embargo, el efecto de la duración del día (es decir, la disponibilidad de luz solar) en los patrones de actividad de las especies que migran latitudinalmente largas distancias, aún no es claro. Aquí nos preguntamos si un aumento de la disponibilidad de luz solar representa un beneficio para los animales que migran largas distancias, al prolongar el periodo de actividad diurna. Para responder a esta pregunta, investigamos si cuatro especies diferentes de aves migratorias de larga distancia, dos migrantes árticos y dos migrantes de latitudes medias, pueden ajustar su actividad diaria y aprovechar los cambios en la duración del día. Cuantificamos la relación entre la actividad diaria (medida con datos de acelerómetro) y la duración del día, y estimamos los patrones de actividad de cada especie. Además, evaluamos el papel de la duración del día como mecanismo último subyacente a la migración de las aves. Las cuatro especies mostraron períodos de actividad más largos durante los días con más horas de luz, mostrando una fuerte relación positiva entre la actividad diaria total y la duración del día. Esta relación varió entre las especies evaluadas. La actividad aumentó en promedio 1.5 veces durante la migración desde las áreas de invernada a las áreas de reproducción. Los mecanismos subyacentes a estas relaciones revelan dos patrones de actividad diaria. Las especies que forrajean en vuelo mostraron un aumento en su patrón de actividad. En este caso, la actividad diurna aumentó uniformemente hasta el mediodía y disminuyó hasta el atardecer, mostrando una pendiente de actividad específica para la estación. De otro lado, las especies que forrajean en tierra mostraron un patrón de actividad constante. Según este patrón, la actividad diurna aumenta hasta un determinado nivel, a partir del cual se mantiene durante el resto del día. Nuestro estudio revela que el aumento en la longitud del día le permite a las aves prolongar su actividad e incrementar su actividad diaria total. Estos resultados señalan que la disponibilidad de luz diurna podría ser otro mecanismo último subyacente a la migración de las aves y puede actuar como un factor de selección en la evolución de la migración.